Integrating Physical Activity into a Nutrition and Exercise Science Middle School Curriculum: The THINK Program. - Perry, Arlette; Bonner, Joseph; Williams, Sophia; Xiong, Wei; Garcia, Alejandro; Velasquez, Carolina; Friedman, Alexis; Lee, Debbiesiu L.; Hernandes, Ingrid de Lima; Shen, Ji; Meyer, Marisol; Fernandez, Lucia (Nutrients, 2025)
Background/Objectives: Recent interest has emerged in novel initiatives that focus on the "whole child" to improve the health and well-being in youth. The purpose of this study was to determine whether a translational health in nutrition and kinesiology (THINK) program addressing physical, psychological, and educational well-being could improve personal health and lifestyle behaviors in youth. Methods: A total of 81 adolescents (44 males, 37 females, 12.50 + 0.62 years) were evaluated at the beginning and end of the spring semester across three different years: 2019, 2021, and 2023. The physical literacy measures included the Physical Activity Enjoyment Scale (PAES) and the Physical Activity Perception Scale (PAPS), along with knowledge-based tests in nutrition and exercise science. Social emotional learning (SEL), STEM education, and nutrition habits were evaluated using standard surveys and questionnaires. The physical evaluations included measures of body composition and physical fitness. Results: At the completion of the spring semester of each year, evaluations were compiled for all three years, with decreases found for % body fat (p < 0.001) and increases found for lean body mass (p < 0.001). The physical fitness components, including muscular strength (p < 0.001), cardiorespiratory fitness (p < 0.001), power (p < 0.001), and flexibility (p < 0.01), all improved. The physical literacy components, including the PACES (p < 0.001), PAPS (p < 0.001), exercise (p < 0.05), and nutrition science knowledge (p < 0.05) results, also improved. There were no significant changes in any other variables. Conclusions: A novel in-school academic curriculum integrating the physical, psychological, and educational well-being of the whole child could lead to improved body composition, physical fitness, and physical literacy.